PENERAPAN MODEL PENUGASAN KUANTITATIF GUNA OPTIMASI ALOKASI STAF FRONT END (FE) DALAM MEMINIMALKAN WAKTU TRANSAKSI KASIR: Studi Operasional Swalayan Berbasis Komputasi QM for Windows di PT Matahari Putra Prima Tbk - Febri Yanti Simanullang; Jhon Kristopel Manalu; Parapat Gultom (Kampus Akademik Publiser, 2026)
Service speed at the cashier area or Front End (FE) is a crucial parameter in the modern retail industry to maintain customer satisfaction and avoid queue buildup. This study aims to determine the optimal allocation of four FE staff to four regular cashier stations with different machine characteristic loads at PT Matahari Putra Prima Tbk retail outlets. A quantitative approach was applied through the Assignment Model with the parameter of minimizing the average transaction completion time per customer (seconds) using QM for Windows version 5 software. Secondary operational data were obtained from the Point of Sales (POS) system records and sampling observations of product scanning speed by each FE staff. The computational results of the Hungarian algorithm show that staff placement based on the optimal pattern successfully reduced the accumulated transaction duration from 225 seconds to 165 seconds per customer simulation cycle. This efficiency of 26.6% proves the significant contribution of quantitative operations research to the smooth flow of service at the retail Front End area.